Unveiling the Dark Side of Fintech: Challenges and Breaches in Protecting User Data in Indonesia’s Online Loan Services - Admiral, Admiral; Pauck, Mega Ardina (Universitas Negeri Semarang, 2023)
The rapid evolution of information and communication technology has driven diverse business and financial practices. Indonesia is at the forefront with high engagement in fintech online lending services, presenting challenges in safeguarding user data despite these platforms' convenience. This research aims to analyze the intricacies of protecting the personal data of users of online lending services in Indonesia and highlight the obstacles faced in this process. Using a normative legal approach combined with descriptive data analysis, this research examines the protection mechanism from the perspectives of users and online loan service providers. The research concluded that users should verify the legitimacy of online loan service providers by ensuring proper registration with the Financial Services Authority (OJK) of the Republic of Indonesia. In addition, users should carefully scrutinize and understand the terms and conditions of personal data protection before agreeing to an online loan agreement. Second, the main problems qualified as obstacles in this research related to the effectiveness of personal data protection in the context of online lending are at least influenced by three main elements that influence each other, especially those related to legal substance, legal structure, and legal culture. Based on this doctrine, it is found that in addition to legal uncertainty related to the guarantee of personal data protection rights on the one hand, on the other hand, the absence of specialized institutions related to personal data protection is one of the factors that affect the ineffectiveness of personal data protection in Indonesia related to online loans.